2014
DOI: 10.1159/000364903
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Sleep Features of Multiple System Atrophy: Review and Prospective Study

Abstract: Background: The profile and degree of cognitive impairment in Multiple System Atrophy (MSA) and the impact of sleep disorders, REM sleep behavior disorder (RBD) in particular, in parkinsonism-related cognitive deficits are currently being debated. Summary: We reviewed the cognitive, affective and sleep findings in MSA and also carried out a longitudinal investigation of 10 MSA patients. At the first evaluation, 3 patients showed isolated cognitive deficits. After a mean of 16 months, these patients remained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 68 publications
3
33
0
Order By: Relevance
“…This is in agreement with clinical findings on normal amounts of REMS in MSA patients (Vetrugno et al, 2004; Stanzani-Maserati et al, 2014). But old MSA animals spent significantly less amount in REMS than the young MSA mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with clinical findings on normal amounts of REMS in MSA patients (Vetrugno et al, 2004; Stanzani-Maserati et al, 2014). But old MSA animals spent significantly less amount in REMS than the young MSA mice.…”
Section: Discussionsupporting
confidence: 92%
“…REMS latency seems to be decreased in MSA patients (Manni et al, 1993; Plazzi et al, 1997; Stanzani-Maserati et al, 2014). We also found decreased REMS latency in our MSA animals, compared to both control groups.…”
Section: Discussionmentioning
confidence: 99%
“…So far, few studies have addressed the possible differences between patients with predominant cerebellar or parkinsonian presentation, and the focus has been mainly on MSA‐P patients. In this study, a comparison of raw scores revealed lower performance of MSA‐C patients than MSA‐P patients in a screening of executive functions and in phonological verbal fluency.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, severe cognitive decline that significantly disrupts daily living is uncommon in MSA; hence, dementia has been regarded as a nonsupporting feature in the current diagnostic criteria . Comparative studies on cognitive impairment in both motor subtypes have been conducted but reported heterogeneous results . Kawai and colleagues observed a multidomain cognitive decline in MSA‐P but not in MSA‐C .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that RBD is frequent in patients with MSA [8, 10, 16, 22, 26, 27, 32, 33, 36, 37, 40, 41] but its exact prevalence and whether RBD affects all patients with MSA is not known. Moreover, whether questionnaires are sufficient to diagnose RBD or polisomnography showing abnormal muscle activation (i.e., lack of atonia) and vocalizations/motor behavior during REM is required for the diagnosis is unclear.…”
Section: Introductionmentioning
confidence: 99%